Organic‐acid mediated bulk polymerization of ε‐caprolactam and its copolymerization with ε‐caprolactone. Issue 15 (30th March 2016) - Sanchez‐Sanchez, Ana; Basterretxea, Andere; Mantione, Daniele; Etxeberria, Agustin; Elizetxea, Cristina; de la Calle, Amaia; García‐Arrieta, Sonia; Sardon, Haritz; Mecerreyes, David
ABSTRACT: Polyamides (PA) constitute one of the most important classes of polymeric materials and have gained strong position in different areas, such as textiles, fibers, and construction materials. Whereas most PA are synthesized by step‐growth polycondensation, PA 6 is synthesized by ring opening polymerization (ROP) of ε‐caprolactam (ε‐CLa). The most popular ROP methods involve the use of alkaline metal catalyst difficult to handle at large scale. In this article, we propose the use of organic acids for the ROP of ε‐CLa in bulk at 180 °C (below the polymer's melting point). Among evaluated organic acids, sulfonic acids were found to be the most effective for the polymerization of ε‐CLa, being the Brønsted acid ionic liquid: 1‐(4‐sulfobutyl)−3‐methylimidazolium hydrogen sulfate the most suitable due to its higher thermal stability. End‐group analysis by 1 H nuclear magnetic resonance and model reactions provided mechanistic insights and suggested that the catalytic activity of sulfonic acids was a function of not only the acid strength, but of the nucleophilic character of conjugate base as well. Finally, the ability of sulfonic acid to promote the copolymerization of ε‐CLa and ε‐caprolactone is demonstrated. As a result, poly(ε‐caprolactam‐ co ‐ε‐caprolactone) copolymers with considerably randomness are obtained. This benign route allows the synthesis of poly(ester amide)s with different thermal and mechanical properties. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2394–2402 Abstract : In this work, organic acids were explored for the ring‐opening polymerization of ε‐caprolactam (ε‐CLa) in bulk at 180 °C (below the polymer's melting point) to give the commercially important product PA 6. Among organic acids investigated, sulfonic acids were found the most effective for the polymerization of ε‐CLa being the Brønsted (sulfonic) acid ionic liquid: 1‐(4‐sulfobutyl)−3‐methylimidazolium hydrogen sulfate the most active one. Under optimum conditions, ε‐CLa was copolymerized with ε‐caprolactone to obtain biodegradable poly(ester amide)s. It is found that poly (ε‐caprolactam‐ co ‐ε‐caprolactone) copolymers with considerable randomness are formed.